If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(2b + 1) + -6b = 0 Reorder the terms: 2(1 + 2b) + -6b = 0 (1 * 2 + 2b * 2) + -6b = 0 (2 + 4b) + -6b = 0 Combine like terms: 4b + -6b = -2b 2 + -2b = 0 Solving 2 + -2b = 0 Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + -2b = 0 + -2 Combine like terms: 2 + -2 = 0 0 + -2b = 0 + -2 -2b = 0 + -2 Combine like terms: 0 + -2 = -2 -2b = -2 Divide each side by '-2'. b = 1 Simplifying b = 1
| a=(3.14)(16) | | -y^4-2y=0 | | -2y^4-4y=0 | | a=(1/2)(24)(26) | | 16x^2+1100x-6050=0 | | 7x+6=-2y-14x | | 8x+y+4=0 | | x+2*x+2=2x+3 | | x^2+y^2+8x=6 | | (7x^4y-3y^8)dx+(2x^5-9xy^7)dy=0 | | -200.00+25.00x=50 | | 12y=5x-3 | | -200.00+25.00x=0.00 | | y-24=-1.2(x-2) | | 1/a=6/18 | | 1/8=20/x | | 6xy-12x=0 | | 1/8=x/20 | | 1/10=15/x | | -x^2+740x-230=0 | | x^2-740x+230=0 | | y-55=-1.4(x-5) | | y=5x/x+2 | | (((4-4x)/(x^2+2x-3))+x)=0 | | 8/5-1/5x | | ((4-4x)/(x^2+2x-3))+x=0 | | 120=(2x-1)*y | | 120=2x-1*y | | (x^2-9)(6x+1)=0 | | -3/4n+3n=3/2n-13/3 | | -500.00+5.00x=600.00 | | -500.00+5.00x=750.00 |